PENGARUH CITY BRANDING “SHINING BATU” TERHADAP CITY IMAGE DAN KEPUTUSAN BERKUNJUNG WISATAWAN KE KOTA BATU TAHUN 2014 - Lita Ayu Wandari (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
This research aims to: investigate the influence of city branding on city image; investigate the influence of city branding on decision to visit; and investigate the influence of ity image on decision to visit. The research method used in this study is explanatory reserach. Sample of 102 tourists visiting the tourist attractions in Batu 2014 purposive random sampling technique. Methods of data collection questionnaire. Descriptive data analysis and path analysis. The results showed that the variables significantly influence city branding of city image; city ​​branding variables significantly influence decision visit; and variable city image but no significant effect on the decision to visit. Based on these results it is suggested City Branding Stone City should continue to be published to the public so that people understand the meaning of the brand of Batu City